Teacher Parenting Patterns in Improving Students' Ability to Memorize Al-Qur'an in Tahfidz Elementary School - Siti Lailatul Nafisah; Suharsiwi Suharsiwi; Mahmudin Sudin (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
The purpose of this study was to describe the parenting style of teachers in improving students' Al-Qur'an memorization skills. The research method uses descriptive qualitative. The research subjects included students aged 7-8 years, parents and teachers at the Shigor Putra Tahfizh Islamic Boarding School Daarul Qur'an Tangerang. Collecting data through observation, interviews, and documentation. The validity of the data was through triangulation, and data analysis was carried out through the stages of reduction, data display and verification. The results of the study concluded that the teacher's upbringing of students in memorizing the Qur'an at SD I'daad Shigor Putra Tahfizh Daarul Qur'an Islamic Boarding School in improving students' ability to memorize the Qur'an is through habituation, with (1) the intention to memorize in the form of prayer, (2) make a target of memorization every day. , (3) reading memorization to friends, and (4) Maintaining memorization by listening to other people's/friends' memorization before submitting it to the teacher